Management of Gastrointestinal Toxicity from Immune Checkpoint Inhibitor - Rocha, Marta (2020)
Immune checkpoint inhibitors have shown anti-tumour activity in cancers such as melanoma, renal cell carcinoma, non-small-cell lung cancer, urothelial carcinoma, colorectal cancer, and Hodgkin's lymphoma. Though immune checkpoint inhibitors have revolutionized the treatment and prognosis of some advanced malignancies, they are also associated with a significant risk of immune-related adverse events. These adverse events can occur in any organ system, but gastrointestinal side effects are among the most commonly reported, with manifestations ranging from mild diarrhoea to severe colitis, sharing some features with inflammatory bowel disease. Anticipating a greater use of these drugs in the future, gastroenterologists should expect to be increasingly faced with gastrointestinal immune-related adverse events. Knowledge of these toxicities, as well as effective management algorithms, is essential to enable early diagnosis and treatment, decreasing morbidity and mortality. We reviewed the currently available literature on gastrointestinal toxicity induced by immune checkpoint inhibitors, namely the clinical features, diagnosis, and management.